Comparison and System Development of a Two-Coil and Three-Coil Inductive Link for Transcutaneous Power Transfer - Maarten Schelles; Ward Lievens; Laurens Goyvaerts; Frederik Ceyssens; Rikky Muller; Michael Kraft (IEEE Access)
Implantable electronic devices are powerful tools to alleviate a range of medical conditions. To minimize the risk of infections and increase patient comfort, no wires should penetrate the skin. For devices with a relatively high power consumption and located right under the skin, wireless power transfer through an inductive link is the most reliable method to ensure robust and long-term functionality. However, the efficiency of these inductive links highly depends on the size, location and variable power consumption of the implant. Here, we developed a functional prototype for the application of a neurostimulator implant located subcutaneously in a recess in the skull. Keeping all geometric constraints constant, we investigated the differences between a two-coil and three-coil inductive link, showing that the two-coil system has a higher peak efficiency of the inductive link of 84%, while the three-coil system displays a flatter efficiency curve with a peak of 78%, as a function of the variable power consumption. Furthermore, we have developed a closed-loop electronic system to drive the link at a fixed frequency of 27.12 MHz, with an overall system efficiency of 30%. Our results demonstrate the advantages and disadvantages of using two-coil and three-coil inductive links, as well as the possibility to use these to transmit 60 mW to a subcutaneous implant. Such efficient and robust transcutaneous power transfer will allow for the development of safer and more patient-friendly implantable devices.